2014
DOI: 10.1002/2013jd020932
|View full text |Cite
|
Sign up to set email alerts
|

Projections of future summertime ozone over the U.S.

Abstract: We use a regional coupled chemistry-transport model to assess changes in surface ozone over the summertime U.S. between present and a 2050 future time period at high spatial resolution under the A2 climate and Representative Concentration Pathway (RCP) 8.5 anthropogenic precursor emission scenarios. Predicted changes in regional climate and globally enhanced ozone are estimated to increase surface ozone over most of the U.S.; the 95th percentile for daily 8 h maximum surface ozone increases from 79 ppb to 87 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 125 publications
(155 reference statements)
3
104
2
Order By: Relevance
“…There is some debate as to the magnitude of any climate penalty; for example, the study of Tai et al (2013) indicates that, in the presence of CO 2 -isoprene interaction, the projected change in isoprene emission by 2050 will be largely offset or even reverse in sign, leading to much reduced sensitivity of ozone and SOA (by > 50 %) to climate and natural vegetation. Bloomer et al (2009) estimated the magnitude of these effects from surface ozone observations over the US at about 2.2 ppb per degree Celcius and Pfister et al (2014) showed increasing summertime ozone levels under various climate scenarios. These effects have been quantified over Europe in several model studies Meleux et al, 2007;Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013bKatragkou et al, 2011).…”
Section: Hemispheric Transport Of Ozone and It Precursors In The Polimentioning
confidence: 99%
“…There is some debate as to the magnitude of any climate penalty; for example, the study of Tai et al (2013) indicates that, in the presence of CO 2 -isoprene interaction, the projected change in isoprene emission by 2050 will be largely offset or even reverse in sign, leading to much reduced sensitivity of ozone and SOA (by > 50 %) to climate and natural vegetation. Bloomer et al (2009) estimated the magnitude of these effects from surface ozone observations over the US at about 2.2 ppb per degree Celcius and Pfister et al (2014) showed increasing summertime ozone levels under various climate scenarios. These effects have been quantified over Europe in several model studies Meleux et al, 2007;Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013bKatragkou et al, 2011).…”
Section: Hemispheric Transport Of Ozone and It Precursors In The Polimentioning
confidence: 99%
“…2. The number and/or frequency of events above a fixed value that is considered extreme at present, including values that are relevant to attaining ambient air quality standards (AAQS) (e.g., Murazaki and Hess, 2006;Wu et al, 2008;Gao et al, 2013;Pfister et al, 2014;Rieder et al, 2015). 3.…”
Section: State Of Knowledgementioning
confidence: 99%
“…While evaluations applying a range of the approaches above show that global models are generally able to represent the salient features of extreme ozone episodes including extent, duration, frequency and year-to-year variability (e.g., Fiore et al, 2003;Schnell et al, 2015), there are systematic regional biases in the intensity of ozone extremes, especially for the summertime eastern U.S. (e.g., Rasmussen et al, 2012;Pfister et al, 2014;Rieder et al, 2015). As stated above, these biases are most problematic when focusing on ozone extremes defined as number or frequency above a fixed threshold or AAQS metric.…”
Section: State Of Knowledgementioning
confidence: 99%
See 2 more Smart Citations